Impact of tropical cyclone Amang on variability of wind speed, salinity, sea surface temperature, and their relationship to chlorophyll-a in sea waters of Sangihe Island - Rachim, M. Hatta; Schaduw, Joshian N.W.; Wantasen, Adnan S.; Patty, Wilhelmina; Ngangi, Edwin L.A (Universitas Sam Ratulangi, 2021)
High concentrations of chlorophyll-a can be used to predict where fish gather. On the other hand, tropical cyclones are one of the triggering factors for vertical stirring and upwelling that cause fertility of waters. The Sangihe Island area is not an effective area for the formation of tropical cyclones. However, due to its geographical location with a tropical cyclone area and trajectory, the potential for disturbances caused by cyclones is impactful on Sangihe Island. The distribution of wind speed, salinity, sea surface temperature and chlorophyll-a concentration can be detected by satellite remote sensing imagery. This study aims to analyze the impact of Tropical Cyclone Amang on the variability of wind speed, salinity, sea surface temperature and on the concentration of chlorophyll-a in Sangihe Island. This study useswind speed, salinity, sea surface temperature and chlorophyll-a data during the Amang Tropical Cyclone (January 6-27, 2019) from the AQUA-MODIS satellite imagery. The results show that the relationship between wind speed and chlorophyll-a concentration has impact on other parameters where both parameters showed a strong correlation value. It was also showed on the relationship between sea surface temperature and chlorophyll-a.However, the relationship between salinity and chlorophyll-a concentration showed lowest effect among those parameters.Indonesian title:Â Dampak siklon tropis Amang terhadap variabilitas kecepatan angin, salinitas, suhu permukaan laut, dan hubungannya dengan klorofil-a di perairan laut Pulau Sangihe